2019
DOI: 10.21791/ijems.2019.1.42.
|View full text |Cite
|
Sign up to set email alerts
|

Determination of different parameters to high strength steel clinch joints by FEA

Abstract: In this article the clinched joints were analyzed by finite element method (FEA). The base materials were advanced high strength steels (DP 600, DP 800 and DP 1000). The model validation procedure was done by the DP 600 type of steel sheets; the other two types of steel were only simulated. The goal was to determine the geometrical properties of the joints with different strength steels. The FEA model was the same in every mechanical point of view therefore the results are comparable. The main geometrical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Flodr et al [96], Berezhnoi et al [97], and Jonas et al [98] studied the mechanical properties of the clinched joint using the finite elements method. The authors found the functional relationship between forming force and geometry of clinched joint.…”
Section: Steel Sheetmentioning
confidence: 99%
“…Flodr et al [96], Berezhnoi et al [97], and Jonas et al [98] studied the mechanical properties of the clinched joint using the finite elements method. The authors found the functional relationship between forming force and geometry of clinched joint.…”
Section: Steel Sheetmentioning
confidence: 99%
“…Ebben az összesítő tanulmányunkban az alumínium-acél lemezpárosítást vizsgáljuk, de például [9] cikkben az eltérő szilárdságú lemezek kötéseiről írtunk.…”
Section: Eltérő Anyagok Klincseléseunclassified
“…Finite element analysis (FEA) is valuable to analyse the clinching problem, but effortful and difficult to verify in this situation due to the asymmetrical geometry and nonlinear plasticity. Examples of FEA clinch models are [ 31 , 32 , 33 , 34 ]. Hence, there is value in considering other methods that can elucidate the flow of material in the plastic deformation, especially methods that are quick to deploy.…”
Section: Introductionmentioning
confidence: 99%